CLO3D and posthumanism: rethinking the relationship between body, fabric, and digital space in Malaysian fashion - Saleh, Maarof; Baharudin, Anis Nadiah; Ahmad, Hasma; Ainaidu, Reyilan (Universiti Teknologi MARA, Perak, 2025)
This study examines how CLO3D, a 3D fashion design software, reconfigures the relationship between body, fabric, and cultural identity in Malaysia’s fashion industry through a post-humanist lens. By analysing qualitative interviews with six Malaysian designers and visual-textual artifacts from CLO3D projects, the research reveals three transformative dynamics: (1) the emergence of digital corporeality, where non-normative avatars disrupt anthropocentric ideals of the body; (2) distributed agency between human designers and algorithmic tools, challenging traditional notions of authorship; and (3) the hybridization of cultural heritage, as motifs like batik and songket merge with cyber-digital aesthetics. Findings demonstrate CLO3D’s dual role as a decolonial tool for subverting Eurocentric fashion hierarchies and a neoliberal force that risks commodifying cultural symbols. The study highlights tensions between sustainability and digital consumerism, as well as debates over the devaluation of artisanal craftsmanship in virtual workflows. By centering Malaysia’s postcolonial context, this article addresses gaps in non-Western perspectives on digital fashion. It concludes with recommendations for integrating post-humanist frameworks into ASEAN fashion pedagogy, fostering ethical digital preservation of cultural heritage, and advocating for green technologies to mitigate CLO3D’s environmental footprint. This research contributes to broader discourses on technology’s role in redefining identity, materiality, and agency in Global South creative industries.